Build systems à la carte: Theory and practice. (21st April 2020) - MOKHOV, ANDREY; MITCHELL, NEIL; PEYTON JONES, SIMON
Abstract: Build systems are awesome, terrifying – and unloved. They are used by every developer around the world, but are rarely the object of study. In this paper, we offer a systematic, and executable, framework for developing and comparing build systems, viewing them as related points in a landscape rather than as isolated phenomena. By teasing apart existing build systems, we can recombine their components, allowing us to prototype new build systems with desired properties.